(untitled) (Docentes 2.0 Journal, 2023)
Strategic planning is a key element to improve the management of educational organizations both internally and externally. Various organizations have pointed out this, highlighting the importance of providing higher-quality educational services. Therefore, the objective of the research was to analyze the trends of strategic planning in the management of early education schools in Peru. Under a descriptive quantitative approach, research that used the positivist paradigm was supported by a meta-analysis and a cross-sectional experimental design. Consequently, the content analysis methodology used was based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, based on access to ten articles from specialized scientific journals indexed in the electronic databases Scopus, Web, Science, Redalyc, and Scielo. In conclusion, the results provided some reflections on the concept of strategic planning as an educational practice that surpasses traditional approaches by being dynamic, comprehensive, and inclusive, guaranteeing the success of school management processes at the initial level.